Transformation of the Capacity and Institutions of Fishing Communities Through Knowledge Transfer and the Formation of Freshwater Eel Cultivation Interest Groups in Magetan Regency - Emiliana Sri Pudjiarti; Enny Nurlaili; Stefanus Topan Wijaya; Bintang Kartikasari (Abdimas Indonesian Journal, 2025)
This community service activity aims to increase the knowledge and skills capacity of fishing communities in Magetan Regency through cross-generational knowledge transfer, from conventional approaches to data-based and digital approaches, and facilitate the formation of freshwater eel cultivation interest groups as new institutional forums. The activity was held for two days, January 3 and 4, 2025, attended by 25 participants from Magetan, Bogor, Lampung, Sukabumi, Majalengka, Pandawan (Malang), Sidoarjo, Pacitan, and Jakarta. The implementation phase included preparation and needs surveys, cross-generational dialogue on the first day regarding eel biology and stages of multi-level rearing, namely glass eels in aquariums, followed by elvers, fingerlings, and consumption in ponds, each for four months, and the second day consisted of simulations of business results and profits, product diversification, digital marketing strategies, and a group formation forum. The discussion increased participants' knowledge scores from 42 to 78. A business simulation of 1,000 glass eel seeds yielded an estimated harvest of 300 kilograms and a net profit of around Rp 16,500,000. The identification of alternative processed products, such as smoked and shredded eel, and the formation of the Lawu Sejahtera Sidat Group, complete with a management structure and initial work plan. It is recommended that ongoing technical assistance, facilitation of capital access, and advanced training in product processing be provided to ensure that the capacity and institutional transformation achieved can continue to develop independently and sustainably in Magetan Regency.